Regional quantification of muscarinic acetylcholine receptors and β-adrenoceptors in human airways - Ikeda, T (Blackwell Publishing Ltd, 2012)
BACKGROUND AND PURPOSE: Muscarinic acetylcholine receptors (mAChRs) and β-adrenoceptors in the airways and lungs are clinically important in chronic obstructive pulmonary disease (COPD) and asthma. However, the quantitative and qualitative estimation of these receptors by radioligand binding approaches in human airways has not yet been reported because of tissue limitations. EXPERIMENTAL APPROACH: The regional distribution and relative proportion of mAChR and β-adrenoceptor subtypes were evaluated in human bronchus and lung parenchyma by a tissue segment binding method with [(3)H]-N-methylscopolamine ([(3)H]-NMS) for mAChRs and [(3)H]-CGP-12,177 for β-adrenoceptors. Functional responses to carbachol and isoprenaline were also analysed in the bronchus. KEY RESULTS: The M(3) subtype predominantly occurred in the bronchus, but the density decreased from the segmental to subsegmental bronchus, and was absent in lung parenchyma. On the other hand, the M(1) subtype occurred in the lung only, and the M(2) subtype was distributed ubiquitously in the bronchus and lungs. β(2)-adrenoceptors were increased along the airways, and their densities in the subsegmental bronchus and lung parenchyma were approximately twofold higher than those of mAChRs in the same region. β(1)-adrenoceptors were also detected in lung parenchyma but not in the bronchus. The muscarinic contractions and adrenoceptor relaxations in both bronchial regions were mediated through M(3)-mAChRs and β(2)-adrenoceptors, respectively. CONCLUSIONS AND IMPLICATIONS: From the present radioligand binding approach with intact tissue segments, we constructed a distribution map of mAChRs and β-adrenoceptors in human bronchus and lung parenchyma for the first time, providing important evidence for future pharmacotherapy and new drug development for respiratory disorders.